OXTR moderates adverse childhood experiences on depressive symptoms among incarcerated males - Zhang, Jieting (2021)
Objectives: This study examined the moderation of an oxytocin receptor (OXTR) gene in the link between childhood adversity and depressive symptoms among incarcerated males. Methods: Questionnaires about adverse childhood experiences and depressive symptoms, as well as genomic DNA from blood were collected among 608 incarcerated males (Mage = 32.4 years, SD = 9.41, 18–74 years). Moderation analysis was applied to examine the interaction between adverse childhood experiences (including abuse, neglect, and household dysfunction) and the OXTR polymorphisms (rs2254298, rs53576) in predicting depressive symptoms. Results: Incarcerated males had relatively higher prevalence of childhood adversity (70.2%) and depressive symptoms (49.8%). Higher childhood adversity was associated with increased depressive symptoms, and the effect was more pronounced in the GG homozygotes of OXTR rs2254298 (b = 0.406, p < .001), as compared with the AA/AG carriers (b = 0.236, p < .001). By contrast, the OXTR rs53576 did not interact with childhood adversity in predicting depressive symptoms. Conclusions: Chinese incarcerated males with the GG genotype of OXTR rs2254298 have higher vulnerability in the effect of childhood adversity on depressive symptoms.